(untitled) (Research, Society and Development, 2024)
Inflammatory bowel disease (IBD), including Crohn’s disease, has a significant genetic basis, highlighted by mutations in protein 2 (NOD2). Thus, these mutations lead to an exaggerated inflammatory response against the intestinal microbiota, involving reactive oxygen species (ROS) and the activation of the PI3K/AKT/PTEN pathway, resulting in the activation of nuclear factor-κB (NF-κB) and production of cytokines, such as TNFα. Thus, this molecular cascade plays a central role in the pathogenesis of Crohn’s disease, making it the target of research for therapeutic development. Furthermore, understanding these molecular interactions may reveal new opportunities for treating the disease. In this sense, this initiative has been the focus of numerous scientific research activities and drug development, in order to establish new targets for therapeutic development against Cronh’s disease.